2021
DOI: 10.3389/fmicb.2021.652276
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characteristics of Staphylococcus aureus From Food Samples and Food Poisoning Outbreaks in Shijiazhuang, China

Abstract: As an opportunistic pathogen worldwide, Staphylococcus aureus can cause food poisoning and human infections. This study investigated the sequence typing, the penicillin (blaZ) and methicillin (mec) resistance profiles of S. aureus from food samples and food poisoning outbreaks in Shijiazhuang City, and the staphylococcal enterotoxin (SE) types of the S. aureus isolates from food poisoning. A total of 138 foodborne S. aureus isolates were distributed into 8 clonal complexes (CCs) and 12 singletons. CC1, CC5, CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…However, our study highlighted the presence of other CCs in European countries, for example, the high prevalence of CC398 in the Netherlands, followed by Germany, Italy, and Denmark, remarks the emerging spread of this clone in these areas. Furthermore, CC1 and CC59 are most prevalent in China, as has been found in previous studies [ 21 , 22 , 23 ], while CC8, CC45, and CC121 were the most abundant in Singapore, Taiwan, and Thailand, respectively. Other studies also described differences among Asian countries, for example, Turner et al (2019) [ 24 ] identified CC8 as a common CC in Korea, CC30 in Japan, and CC59 in Taiwan, while Song et al (2011) [ 25 ] described CC8 as widespread throughout Asian Countries and CC59 mostly isolated in Taiwan [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 73%
“…However, our study highlighted the presence of other CCs in European countries, for example, the high prevalence of CC398 in the Netherlands, followed by Germany, Italy, and Denmark, remarks the emerging spread of this clone in these areas. Furthermore, CC1 and CC59 are most prevalent in China, as has been found in previous studies [ 21 , 22 , 23 ], while CC8, CC45, and CC121 were the most abundant in Singapore, Taiwan, and Thailand, respectively. Other studies also described differences among Asian countries, for example, Turner et al (2019) [ 24 ] identified CC8 as a common CC in Korea, CC30 in Japan, and CC59 in Taiwan, while Song et al (2011) [ 25 ] described CC8 as widespread throughout Asian Countries and CC59 mostly isolated in Taiwan [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 73%
“…S. aureus produces a wide variety of heat-stable staphylococcal enterotoxins (SE) in foods responsible for staphylococcal food poisoning (SFP) in the human population. SFP is characterized by gastroenteritis and has been recognized as one of the main culprits of food poisoning epidemics worldwide [ 39 ]. Methicillin-resistant strains of S. aureus (MRSA) have recently been classified as high priority bacteria with the potential to cause devastating mortality globally if adequate treatment options are not developed [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, other less well-known clones, such as ST6 and ST398, have also been reported. ST6 has been implicated in infectious transmission in communities and hospitals and ST15 in cystic fibrosis patients in China, Europe and the Czech Republic [ 50 , 51 ]. Concerning ST398, which has rarely been described in Algeria [ 44 ], it was initially associated with livestock and subsequently detected in workers in close contact with livestock [ 52 ].…”
Section: Discussionmentioning
confidence: 99%